Comparative biology and growth rate of the mites Mononychellus tanajoa and Euseius ho (Acari) on cassava - RÊGO, ADRIANO S.; MACIEL, ANILDE G. S.; COSTA, ÉVILA C.; SILVA, ESTER A.; TEODORO, ADENIR V. (Revista Colombiana de Entomología, 2012)
The cassava green mite, Mononychellus tanajoa, is an important pest of cassava, Manihot esculenta (Euphorbiaceae), in the northeastern state of Maranhão, Brazil. Predatory mites of the family Phytoseiidae are key natural enemies of pest mites and are found inhabiting cassava plants. We compared some biological aspects and the growth rate of M. tanajoa and the generalist phytoseiid Euseius ho the most abundant predatory mite inhabiting cassava plants in the study region. All experiments were conducted in the laboratory on leaf discs of cassava leaves. The predatory mite was fed in all developmental stages with M. tanajoa. Euseius ho had lower periods of egg, larva, protonymph and deutonymph developmental periods, as well as the period from egg to adult compared to M. tanajoa. Furthermore, the predatory mite E. ho had a high instantaneous rate of increase (ri), yet lower than that observed for its prey, the cassava green mite M. tanajoa. The laboratory results suggest that the predatory mite E. ho may contribute to regulate populations of M. tanajoa in the field.